Bio-milling technique for the size reduction of chemically synthesized BiMnO3 nanoplates - Mazumder, Baishakhi; Uddin, Imran; Khan, Shadab; Ravi, Venkat; Selvraj, Kaliaperumal; Poddar, Pankaj; Ahmad, Absar (Journal of Materials Chemistry, 2007)
Wet- chemical techniques for the synthesis of complex oxide materials have advanced significantly; however, achieving finely dispersed nanoparticles with sizes less than 10 nm still remains challenging, especially for the perovskite family of compounds. On the other hand, a fungusmediated synthesis technique has recently shown potential to synthesize perovskites such as BaTiO3 with sizes as small as 5 nm. Here we report, for the first time, the use of fungal biomass, at room temperature, to break down chemically synthesized BiMnO3 nanoplates ( size similar to 150 - 200 nm) into very small particles (, 10 nm) while maintaining their crystalline structure and the phase purity. This novel technique that we have named as `` bio- milling'' holds immense potential for synergically utilizing both chemical and biological synthesis techniques to synthesize complex oxide nanoparticles with particle sizes less than 10 nm with the proper crystalline phase.

Biosynthesis of fluorescent Bi2S3 nanoparticles and their application as dual-functionSPECT-CT probe for animal imaging - Uddin, Imran; Ahmad, Absar; Siddiqui, Ejaz Ahmad; Rahaman, Sk. Hasanur; Gambhir, Sanjay (Current Topics In Medicinal Chemistry, 2016)
Bismuth sulphide (Bi2S3) is an excellent semiconductor and its nanoparticles have numerous significant applications including photovoltaic materials, photodiode arrays, bio-imaging, etc. Nevertheless, these nanoparticles when fabricated by chemical and physical routes tend to easily aggregate in colloidal solutions, are eco-unfriendly, cumbrous and very broad in size distribution. The aim of the present manuscript was to ecologically fabricate water dispersible, safe and stable Bi2S3 nanoparticles such that these may find use in animal imaging, diagnostics, cell labeling and other biomedical applications. Herein, we for the first time have biosynthesized highly fluorescent, natural protein capped Bi2S3 nanoparticles by subjecting the fungus Fusarium oxysporum to bismuth nitrate pentahydrate [Bi(NO3)(3).5H(2)O] alongwith sodium sulphite (Na2SO3) as precursor salts under ambient conditions of temperature, pressure and pH. The nanoparticles were completely characterized using recognized standard techniques. These natural protein capped Bi2S3 nanoparticles are quasi-spherical in shape with an average particle size of 15 nm, maintain long term stability and show semiconductor behavior having blue shift with a band gap of 3.04 eV. Semiconductor nanocrystals are fundamentally much more fluorescent than the toxic fluorescent chemical compounds (fluorophores) which are presently largely employed in imaging, immunohistochemistry, biochemistry, etc. Biologically fabricated fluorescent nanoparticles may replace organic fluorophores and aid in rapid development of biomedical nanotechnology. Thus, biodistribution study of the so-formed Bi2S3 nanoparticles in male Sprague Dawley rats was done by radiolabelling with Technitium-99m (Tc-99m) and clearance time from blood was calculated. The nanoparticles were then employed in SPECT-CT probe for animal imaging where these imparted iodine equivalent contrast.

Biomimetic synthesis of CdSe nanoparticles with potential bioimaging applications - Ansary, Abu Ayoobul; Uddin, Imran; Khan, Muhammed I. (International Journal of Pharmaceutical Sciences and Research, 2017)
This study presents in vitro biomimetic synthesis of CdSe nanoparticles using the enzyme, NADPH dependent-Nitrate reductase purified from fungus, Fusarium oxysporum. The synthesis of CdSe nanoparticles was accomplished in the presence of a synthetic peptide having amino acid sequence (γ-Glu-Cys-Glu-Cys)-Gly, which acted as binding molecule. The nanoparticles were synthesized in the size range of 3.9–9.0 nm was analysed using TEM. Further characterization of nanoparticles was done using techniques such as UV, PL, XPS, and FTIR. The as-synthesized CdSe nanoparticles were water dispersible containing free reactive amino groups. These CdSe nanoparticles were conjugated with bi-antennary and tri-antennary glycopeptides opening up the possibilities for their applications in bioimaging. These significant observations will help better understand the mechanism of biosynthesis of fluorescent nanoparticles using fungi. These findings promise an alternative strategy for an eco-friendly, economical, and large-scale synthesis of water dispersible CdSe nanoparticles. These CdSe nanoparticles have promising biomedical-imaging applications without a need for further functionalization.